SECURED HANDHELD MOBILE DEVICE COMMUNICATION USING BARCODE MODULATION BASED ON OFDM (International Journal of Engineering and Computer Science, 2018)
The inventions and high end technologies has great impact on digital communication domain which takes wireless communication to next level to support advanced applications and to offer high rates. Although tremendous progress has been registered in past few decades but still handheld mobile communication is concerned area in the wireless communications. Large data encryption in small space and data privacy is two drawbacks leads to manipulations in handheld mobile transmissions. In this paper a DWT based barcode modulation approach is proposed which makes use of DPSK-OFDM as primary resource to yield a secure handheld mobile transmission to support wide range of applications in reliable way. Finally the experimental results show the proposed DWT based mechanism yields low complexity and better performance over Fourier transform and that performance is measured in terms of BER and SNR